Evaluation of Aloe Vera (Aloe vera L.) Gel Preparation Characteristics and Antioxidant Activity Test Using the DPPH Method - Sri Kartini; Reka Octavia; Subardi Bali; Vonny Utama (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Aloe vera (Aloe vera) is a medicinal plant known to possess bioactive compounds with potential antioxidant activity. This study was designed to formulate aloe vera extract into topical gel preparations at different concentrations and to evaluate their antioxidant activity using the DPPH radical scavenging assay. Gel formulations were prepared containing 0% (F0), 1% (F1), and 4% (F2) extract, with Carbopol 940 utilized as the gelling polymer. Physicochemical characterization of the gels included evaluation of pH, viscosity, spreadability, and adhesiveness. Antioxidant activity was quantitatively determined using the DPPH method. The results demonstrated that all gel formulations met organoleptic and pH specifications and exhibited adequate physical stability. Increasing extract concentration led to an increase in viscosity and adhesiveness, accompanied by a reduction in spreadability. The antioxidant assay revealed IC₅₀ values are F0 216.09 µg/mL, F1,147.70 µg/mL, F2 99.75 µg/m and Vitamine C 16.40 µg/mL. These findings indicate that the aloe vera extract gel at a concentration of 4% possesses strong antioxidant activity and appropriate physicochemical properties for topical pharmaceutical application